SUFISM MEANINGS IN THE BRAI ART IN CIREBON - Aditia Muara Padiarta, Anwar Sanusi (IAIN Tulungagung, 2019)
Cirebon as we know for its commerce and name of the city of Wali. Commercially Cirebon is also famous called as the city of shrimp and geographically is labeled to as the center of the earth. Culturally Cirebon is recognized as an art city like other regions in Indonesia. This paper aims at analyzing one of the popular Cirebonese arts called Brai art containing Sufism messages. Brai art is the heritage of Cirebon containing messages of education in managing the mind. The message highlighted in the Brai arts was more on exoteric religious worship. Arts express a sense of a esthetics with God by dancing and praising in five rituals. Every single ‘raka’at’ designates ‘suluk’ to God. This Brai art proves that Cirebon is recognized as the central area for the spread and development of Islam and Sufism because Cirebon has astrategic area both of the Pacific as well as and the maritime area.